Climatology of extreme convective systems in China from joint TRMM and GPM observations - Jiahao Lin; Xiaoteng Huang; Zihao Zhang; Xingyi Lin; Yuhang Hu; Yanbo Wang; Xiaoqun Hu; Fanchao Lyu; Xueke Wu (Atmospheric Research, 2026)

Synergistic architecture and dynamic adaptability in heterogeneous catalysts for CO2 hydrogenation - Jiao Liu; Xingyi Cen; Jiaming Lin; Junrong Yue; Duo Sun; Fang Wang (Journal of Environmental Sciences, 2026)

Monocyte-mediated mechanisms in idiopathic pulmonary fibrosis: opportunities for early intervention - Zhiguo Mao; Ying Liu; Chengfu Han; Xingyi Yang; Xiangke Lin; Shuo Tian; Mingsan Miao (Apoptosis, 2026)

PET imaging-guided biomimetic nanoplatform reprograms the tumor immune microenvironment and disrupts stromal barriers to potentiate immunotherapy in malignancy - Yuan Feng; Wenyu Song; Zhaoguo Lin; Zihan Zhang; Wenzhu Hu; Xingyi Wang; Yueling Deng; Yongkang Gai; Zi Ye; Dawei Jiang; Xiaoli Lan; Xiao Zhang (Chemical Engineering Journal, 2026)

Response and evaluation of polyploidy induction on morphology, physiology and drought tolerance of Hydrangea paniculata ‘Pink Diamond’ - Shizhen Cai; Xingyi Lin; WeiWei Zhou; Shiyuan Xu; Shuju Huang (Euphytica, 2025)

Monoprotonated Rose Bengal: A high-efficiency solar disinfectant for rapid Escherichia coli inactivation in drinking water - Yi Liu; Xingyi He; Qisun Mao; Jiang Xu; Daohui Lin (Journal of Hazardous Materials, 2025)

Degradation of mulch films in different soils and its effects on soil properties and ecotoxicology - Zhe Xu; Lin Zhang; Guangyang Jiang; Xingyi Ding; Yidong Guo; Yongqiang Tian (Environmental Geochemistry and Health, 2025)

Mangrove Transplantation to the North: Carbon Sequestration Capacity—Drivers and Strategies - Kewei Zhou; Yujuan Lv; Yang Gong; Jing Su; Lei Wang; Shengmin Wu; Xi Lin; Qiuying Lai; Yixin Xu; Xingyi Duan (Journal of Marine Science and Engineering, 2025)
Mangroves play a pivotal role in carbon sequestration. To investigate the characteristics and driving factors of carbon sequestration in planted mangrove forests, we focused on planted mangrove forests in Wenzhou City, Zhejiang Province, China. Through a statistical analysis of soil physicochemical properties and plant morphological characteristics, we assessed carbon stock distribution patterns and identified key influencing factors, providing scientific support for the northward expansion of mangroves. The results demonstrated significant differences in soil properties and plant morphological characteristics among different stands (p

Polymeric immunoglobulin receptor (pIgR) in cancer progression: a critical role and potential therapeutic target - Shaoju Qian; Yeqing He; Ruixue Li; Panpan Sun; Xingyi Zhang; Lin Pan; Zhishan Xu; Zhiwei Feng; Rong Lian; Lili Yu (Apoptosis, 2025)

Based on NRCS and the Doppler centroid anomaly in SAR images to retrieve the nearshore bathymetry - Rui Qi; Jiamin Lin; Jian Wang; Xiaonan Yao; Xiaoqing Wang; Xinzhe Yuan; Lei Cui; Peiqing Yang; Xingyi Su (International Journal of Remote Sensing, 2025)

EFNA4-enhanced deubiquitination of SLC7A11 inhibits ferroptosis in hepatocellular carcinoma - Xingyi Zhong; Zhiqin Zhu; Yangfeng Du; Lingzhi Long; Ziping Xie; Yangfeng Zhang; Huijun Yao; Junhao Lin; Fengsheng Chen (Apoptosis, 2025)

Efficient removal of perrhenate/pertechnetate by a pyridinium-based porous polymer - Miaomiao He; Yuxuan Chen; Guangyuan Chen; Wenhao Li; Mingxing Zhang; Chao Zhang; Hao Zhang; Xingyi Long; Kui Tang; Tao Duan; Lin Zhu (Environmental Pollution, 2024)

Flexible self-powered bioelectronics enables personalized health management from diagnosis to therapy - Guang Yao; Xingyi Gan; Yuan Lin (Science Bulletin, 2024)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Flexible and highly piezoelectric nanofibers with organic–inorganic coaxial structure for self-powered physiological multimodal sensing - Xingyi Wan; Zhuo Wang; Xinyang Zhao; Quanhong Hu; Zhou Li; Zhong Lin Wang; Linlin Li (Chemical Engineering Journal, 2023)

Genomic Analysis and Molecular Characteristics in Carbapenem-Resistant Klebsiella pneumoniae Strains - Suying Zhao; Xingyi Qiu; Yiting Tan; Min Xu; Xiaotong Xu; Yulai Ge; Huiling Cao; Min Li; Yuxin Lin; Zhan Zhang; Lei Li; Qian Wu (Current Microbiology, 2022)

Tumor immune checkpoints and their associated inhibitors - Zerui Gao; Xingyi Ling; Chengyu Shi; Ying Wang; Aifu Lin (Journal of Zhejiang University-SCIENCE B, 2022)

Non-linear relationships and interactions of meteorological factors on mumps in Jinan, China - Shaoqian Lin; Shiman Ruan; Xingyi Geng; Kaijun Song; Liangliang Cui; Xiaoxue Liu; Yingjian Zhang; Meng Cao; Ying Zhang (International Journal of Biometeorology, 2021)

Soil nutrient variance by slope position in a Mollisol farmland area of Northeast China - Shaoliang Zhang; Lili Jiang; Xiaobing Liu; Xingyi Zhang; Shicong Fu; Lin Dai (Chinese Geographical Science, 2016)

Dissolution Properties and Physical Characterization of Telmisartan–Chitosan Solid Dispersions Prepared by Mechanochemical Activation - Lin Zhong; Xingyi Zhu; Xiaofang Luo; Weike Su (AAPS PharmSciTech, 2013)